Incorporating the advantages of clickers and mobile devices to teach Economics to non-economists - Hairong Mu; Dimitrios Paparas (Cogent Economics & Finance, 2015)
In the twenty-first century, teaching practitioners in higher education (HE) have found themselves confronted with more challenges to help students engage in learning. Particularly, one of the main problems with the traditional lecture format to teach non-economists economics is that students tend to lack interest in the subject and therefore have a low level of engagement. Student response systems (i.e. "clickers") have been used in classes for about 20 years and become more popular on many college campuses. Many studies reveal that clicker technology offers great promise in increasing students' participation and engagement in lectures. Meanwhile, thanks to fast development of mobile technology, personal mobile devices can be integrated with clicker systems into teaching and learning with improved features. The programme we used and found as a very useful interactive teaching tool for learning is called Kahoot!. This paper offers a brief guidance on how to use Kahoot! to encourage active learning and engage non-economics majors in learning economics. Meanwhile, the existing relevant literature with regard to the use of clickers in HE is highlighted. In addition, the effectiveness of using Kahoot! in teaching economics to non-economists is evaluated by a student survey.
Keywords: 330; clickers; student response system (SRS); mobile technology; economics teaching; student engagement; active learning; economic tools for teaching